2015
DOI: 10.1055/s-0034-1378865
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Amino Acid Based Bifunctional Chiral Tertiary Amines, Quaternary Ammoniums and Iminophosphoranes as Organo­catalysts

Abstract: Acyclic amino acids are one of the most ideal chiral scaffolds for the construction of organocatalysts. The development of acyclic amino acid based bifunctional chiral tertiary amines and their powerful catalytic abilities have been demonstrated in many asymmetric reactions. In this account, we summarize asymmetric transformations promoted by bifunctional chiral tertiary amines according to reaction patterns. Moreover, asymmetric reactions mediated by acyclic amino acid derived quaternary ammoniums as phase-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Enantiomerically pure α‐amino acids are fundamental subunits for peptides and numerous bioactive molecules [34] . Moreover, these compounds are widely used as the precursors of many chiral organocatalysts and ligands [35,36] . In this context, a number of enantioselective catalytic methods have been established, especially for the synthesis of non‐commercially available variants [37,38] .…”
Section: Resultsmentioning
confidence: 99%
“…Enantiomerically pure α‐amino acids are fundamental subunits for peptides and numerous bioactive molecules [34] . Moreover, these compounds are widely used as the precursors of many chiral organocatalysts and ligands [35,36] . In this context, a number of enantioselective catalytic methods have been established, especially for the synthesis of non‐commercially available variants [37,38] .…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was first evaluated in toluene at 25 °C and using L - tert -leucine-based thiourea−tertiary amine I as the catalyst (Table 1, entry 1), with excellent catalytic efficacy as demonstrated in a series of asymmetric reactions [18]. It was found that the reaction was completed after 48 hours, affording the desired [4 + 2] annulation adduct 3a in 55% yield with 64% ee.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has recently devised N -itaconimides for the assembly of succinimide frameworks [1318]. As an extension of these works, herein, we report an asymmetric [4 + 2] annulation reaction of 5 H -thiazol-4-ones with N -itaconimides.…”
Section: Introductionmentioning
confidence: 92%